EDUKASI ASI EKSKLUSIF BAGI IBU HAMIL UNTUK MENINGKATKAN KESIAPAN MENYUSUI DAN KESEHATAN BAYI SEJAK DINI DI KOTA TARAKAN - Reza Bintangdari Johan; Susanti; Idha Farahdiba; Annisa Eka Permatasari; Eka Darmayanti Putri Siregar (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Infant Mortality Rate (IMR) still poses a health concern in Indonesia, including in Tarakan, some cases are caused by infections and diarrhea. Exclusive breastfeeding can help prevent these conditions in infants. The extent of this practice can be observed through exclusive breastfeeding coverage in the community. Limited maternal understanding of the advantages of breastfeeding for both the baby and the mother is frequently linked to low coverage. One effective strategy to address this issue is providing structured and effective education. This activity aimed to improve pregnant women’s understanding of exclusive breastfeeding. It was conducted on August 23, 2024, at the home of a community health volunteer in Juata Laut Subdistrict, North Tarakan. The method was a lecture combined with a health education approach and was attended by seven pregnant women and held alongside a routine antenatal class. The assessment instrument used was a 15-item questionnaire on exclusive breastfeeding, with a validity score of 0.973. Three stages made up the activity: preparation, carrying out the activity, and post-test evaluation. Results showed that 5 out of 7 participants (71%) had good knowledge of exclusive breastfeeding. However, 4 participants (57%) believed that breastfeeding leads to weight gain, 1 participant (14%) did not recognize its role in preventing breast cancer, and 5 participants (71%) were unaware of its contraceptive function. Health education proved effective in increasing knowledge, though continued and comprehensive efforts during pregnancy are needed to support optimal breastfeeding practices.